Implementation of Student Team Achievement Divisions (STAD) Learning Methods to Improve Nahwu Learning Outcomes for Class 4 Students at KMI Darussalam Gontor Modern Islamic Boarding School for Girls - Ihwan Mahmudi; Sammay Alfi; Azhar Nor (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2022)
This study aims to determine the effectiveness of the Student Team Achievement Divisions (STAD) method in improving the learning outcomes of Naḥwu for KMI Islamic Boarding School Darussalam Gontor Students. The research subjects were students of KMI class 4E. This research uses classroom action research (CAR) with Kemmis and McTaggart models. The research was conducted in three cycles, and each cycle consisted of four stages: planning, action, observation, and reflection. The results of the study showed that the application of theStudent Team Achievement Divisions (STAD) method couldimprove the learning outcomes of Naḥwu students of Kulliyyatu l-Mu'allimat Al-Islamiyah (KMI) Islamic Boarding School Darussalam Gontor for Girls campus onethe academic year 1440-1441 H. Although there was a decline at the cycle stage 2 after being developed and improved again, the Student Team Achievement Divisions (STAD) method can significantly increase the value of student learning outcomes. It can increase student activity in the learning process. Student learning outcomes in the first cycle with an average of 85, in the second cycle with an average of 83.1, and in the third cycle with an average of 90.45. These results indicate that the average cycle I to cycle II decreased and increased after the third cycle was held. Keywords: Learning Methods, Student Team Achievement Divisions (STAD), Learning Outcomes, Naḥwu. Abstrak Penelitian ini bertujuan untuk mengetahui efektifitas metode Student Team Achievement Divisions (STAD) dalam meningkatkan hasil belajar Naḥwu pada Siswi KMI Pondok Modern Darussalam Gontor. Subjek penelitian adalah siswi KMI kelas 4E. Penelitian menggunakan jenis penelitian tindakan kelas (PTK) dengan model Kemmis dan McTaggart. Penelitian dilakukan dalam tiga siklus, dan setiap siklus terdiri dari empat tahapan yaitu: perencanaan, tindakan, observasi, dan refleksi. Hasil dari penelitian menunjukkan bahwa penerapan metode Student Team Achievement Divisions (STAD) dapat meningkatkan hasil belajar Naḥwu siswi Kulliyyatu-l-Mu’allimat Al-Islamiyah (KMI) Pondok Modern Darussalam Gontor Putri kampus 1 tahun ajaran 1440-1441 H. Meskipun terjadi penurunan pada tahap siklus 2 namun setelah dikembangkan dan diperbaiki kembali metode Student Team Achievement Divisions (STAD) dapat meningkatkan secara signifikan nilai hasil belajar siswa dan dapat meningkatkan keaktifan siswa dalam proses pembelajaran. Hasil belajar siswi pada siklus I dengan rata-rata 85, pada siklus II dengan rata-rata 83,1, dan pada siklus III dengan rata-rata 90,45. Dari hasil tersebut menunjukan bahwa rata-rata siklus I ke siklus II menurun, dan setelah diadakan siklus III mengalami peningkatan. Kata Kunci: Metode Pembelajaran, Student Team Achievement Divisions (STAD), Hasil Belajar, Naḥwu.